FSMP-18. COMPREHENSIVE METABOLIC PROFILING OF HIGH MYC MEDULLOBLASTOMA REVEALS KEY DIFFERENCES BETWEEN IN VITRO AND IN VIVO GLUCOSE AND GLUTAMINE USAGE. (25th March 2021) - Pham, Khoa; Poore, Brad; Hanaford, Allison; Maxwell, Micah J; Sweeney, Heather; Parthasarathy, Akhila; Alt, Jesse; Rais, Rana; Slusher, Barbara S; Eberhart, Charles G; Raabe, Eric H
Abstract: Reprograming of cellular metabolism is a hallmark of cancer. Altered metabolism can overcome unfavorable conditions, allowing cancer cells to proliferate and invade in different tumor microenvironments. Medulloblastoma is the most common malignant brain tumor of children. Genomic amplification of MYC is a hallmark of a subset of poor-prognosis medulloblastoma. However, the metabolism of high MYC amplified medulloblastoma subgroup remains underexplored. We performed comprehensive metabolic studies of human MYC-amplified medulloblastoma by comparing the metabolic profiles of tumor cells in different environments – in vitro, in flank xenografts and in orthotopic xenografts. Principal component analysis showed that the metabolic profiles of brain and flank high-MYC medulloblastoma tumors clustered closely together and separated away from normal brain and the high-MYC medulloblastoma cells in culture. Compared to normal brain, MYC-amplified medulloblastoma orthotopic brain tumor xenografts showed upregulation of nucleotide, amino acid and glutathione pathways. Glucose was the main carbon source for the nucleotide synthesis and the TCA cycle in vivo . The glutaminase ii pathway was the main pathway utilizing glutamine in MYC-amplified medulloblastoma. In brain and flank xenografts, glutathione was the most abundant upregulated metabolite. Glutamine derived glutathione was synthesized through glutamine transaminase K (GTK) enzyme in vivo . The glutamine analog 6-diazo-5-oxo-l-norleucine (DON) significantly inhibited glutathione, amino acid, and nucleotide synthesis. In conclusion, we found that MYC-amplified medulloblastoma relied on glutamine metabolism in synthesizing glutathione in vivo . Glutamine antagonists may have therapeutic applications in human patients.